DIDACTIC POTENTIAL OF TRAINING TECHNOLOGY IN DEVELOPING ENGLISH-SPEAKING STRATEGIC COMPETENCE OF FUTURE TRANSLATORS - Морська, Л.; Сабат, Н. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
Foreign language education of specialists in the field of translation requires the use of intensive technologies that take into account the strategic basis for the development of a professionally oriented communicative competence of future translators, in particular, the professional education of translators in oral forms of translation (synchronous and consecutive). Effective in the light of the above mentioned, the research has proved a methodology that involves the use of training technology. The article explores the essence of the training technology and outlines its didactic potential for the development of English-language strategic competence in future translators. The efficiency of this technology has been proved in view of a number of advantages for the professional foreign language education of specialists in the field of translation, in particular, the possibility of simulating the situations of professional activity of the training participants, systematization of acquired knowledge, formed habits, skills, and partial competencies, ensuring a rapid pace of learning activity, awareness of the level of one’s own professional competence, outlining the ways of personal professional self-development. All of the above mentiioned aspects determine the achievement of the maximum didactic result for the minimum academic time spent. The article proposes and describes an indicative training program for the development of English-language strategic competence of future translators consisting of five blocks of the so-called micro-trainings (memory training, training of switching from one language to another, training of the pace of speech, training of compression and deployment of text, multilingual conference training), each of which presents examples of typical exercises and tasks for students to perform during individual and group work while accomplishing training sessions. The range of translation strategies the formation of which is aimed by a particular micro-training has been determined